Análise dos fatores de convencimento do juízo brasileiro quanto à ocorrência de fraude contábil: um estudo de caso Múltiplo da Gallus, da Encol e do Banco Santos - Moura, Denia de (2007)
This work is based on the analysis of three Brazilian cases of condemnation by accounting fraud and financial reports manipulation of data, where we tried to identify if there is condemnation by accounting fraud in Brazil and the main factors considered by the judge to convince them about the accounting fraud. The theoretical reference quoted involves the theory of fraud, the psychology of fraud, examples of financial fraud in foreign companies and Brazilians banks and the law in Brazil regarding fraud and money laundering. The methodology consisted in studies of Brazilian cases with the data collection criteria from three law suits. The methodology used was the Contents Analysis The samples were chosen according to the impact those cases had in Brazil and the facility to access their law suits. Therefore, we chose Gallus Agropecuária S/A, Encol S/A and Banco Santos S/A for a matter of convenience. The evidence indicated that in those three cases, the court was convinced by the accounting fraud due to omission of relevant financial information in the balance sheet, by information provided to the market that didn¿t reflect the healthy of the company (assets written up without the property). It was identified as well that, in those three cases, there was condemnation not only for the accounting fraud per si, but also by the combination of other crimes as money laundering, fraud gang, material and ideological false fraud, and bankruptcy.